An in vitro comparison of root canal transportation by reciproc file with and without glide path. - Kiumars Nazarimoghadam; Mohammad Daryaeian; Nahid Ramazani (Tehran University of Medical Sciences, 2014)
The aim of ideal canal preparation is to prevent iatrogenic aberrations such as transportation. The aim of this study was to evaluate the root canal transportation by Reciproc file with and without glide path.Thirty acrylic-resin blocks with a curvature of 60° and size#10 (2% taper) were assigned into two groups (n= 15). In group 1, the glide path was performed using stainless steel k-files size#10 and 15 at working length In group 2, canals were prepared with Reciproc file system at working length. By using digital imaging software (AutoCAD 2008), the pre-instrumentation and post-instrumentation digital images were superimposed over, taking the landmarks as reference points. Then the radius of the internal and external curve of the specimens was calculated at three α, β and γ points (1mm to apex as α, 3mm to apex as β, and 5mm to apex as γ). The data were statically analyzed using the independent T-test and Mann-Whitney U test by SPSS version 16.Glide path was found significant for only external curve in the apical third of the canal; that is, 5mm to apex (P=0.005). But in the other third, canal modification was not significant (P> 0.008).Canal transportation in the apical third of the canal seems to be significantly reduced when glide path is performed using reciprocating files.